Gerakan Sosial Kaum Santri Melawan Rencana Penambangan di Paseban - Amal, M Khusna (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
This paper examines the involvement of santri in protesting against the government's policy on the exploration of iron sand mines in Paseban, Jember. Unlike previous studies that tended to saw protest as a form of group struggle and/or sosial class oriented to gain (in a materialistic sense), the protests movements supported by santri activists were not that simple. The study has shown that the protests by the santri in fact have a pluralistic goals, including a counter to government policies that are considered more pro-capitalists, protect the fate of the grassroots community from the impact of mining, and maintain coastal ecological sustainability. Another interesting finding is that santri use religion in their protest not merely as a theological weapon, but rather as a source of ethics, morals and spirit of resistance. Of course, this fact can corrects the commodification theory which always sees the use of religion by agencies in relation to the struggle to accumulate capital